Cross talk between the glucocorticoid receptor and the progesterone receptor in modulation of progestin responses and HIV-1 infection - Bick, Alexis J (Department of Molecular and Cell Biology, 2018)
Current epidemiological data showing that the use of the injectable contraceptive progestin Depotmedroxyprogesterone acetate (DMPA) is associated with increased HIV-1 acquisition is controversial. However, animal and ex vivo data reveal plausible biological mechanisms whereby MPA may increase HIV-1 acquisition. Relatively high levels of endogenous progesterone (P4) found in the luteal phase of the menstrual cycle have also been linked to increased HIV-1 acquisition in animal, clinical and ex vivo models. One of the central hypotheses of the present study was that the mechanism of MPA-induced increase in HIV-1 infection occurs via a different mechanism to that of the luteal phase. Furthermore, MPA has been shown to activate both the glucocorticoid receptor (GR) and its target, the progesterone receptor (PR) isoform B (PR-B), which are both transcription factors and regulate genes involved in immune function. Both the GR and PR are expressed in the cervix, the primary site of heterosexual HIV-1 infection. PR is regulated by endogenous estrogen (E2), of which the concentrations fluctuate throughout the menstrual cycle, and GR expression also varies in response to stress hormones, leading to conditions of varied relative levels of GR/PR. The immune-related consequences of changing the relative levels of GR and PR-B are not well understood. Therefore another hypothesis of this study was that changing the relative levels of GR/PR-B modulates HIV-1 infection and immunomodulatory gene expression in response to the GR/PR agonist, MPA. Since GR and PR-B recognize similar DNA target sequences and may regulate the same genes at the same time, the final hypothesis of the present study was that GR and PR-B reciprocally modulate each other’s activity, through possible association. To investigate the effects of exogenous hormones on HIV-1 infection and mechanisms thereof, peripheral blood mononuclear cells (PBMCs) and TZM-bl cervical cells were used as model systems for HIV-1 infection. These cells were stimulated with P4 and E2 at concentrations mimicking the menstrual cycle phases or with levels of MPA at the upper range of peak serum levels detected in DMPA users. Cells were infected with the R-tropic HIV-1 infectious molecular clone, HIV-1Bal_Renilla and luciferase assays were used to measure HIV-1 infection. Levels of HIV-1 CD4 receptor and CCR5 co-receptor protein or mRNA were measured by flow cytometry or qPCR, respectively, while activation of CD4+ T cells using the activation marker CD69 was measured by flow cytometry in PBMCs. To investigate the effects of changing GR/PR-B levels on HIV-1 infection and immune gene regulation, GR/PR levels were altered in End1/E6E7 immortalized endocervical and HeLa/TZM-bl cervical carcinoma cells by GR siRNA knockdown with or without the simultaneous over-expression of PR-B, and cells were stimulated with MPA or the GR agonist Dexamethasone. mRNA expression iii of key immunomodulatory genes in End1/E6E7 and HeLa cells was measured by qPCR. The modulation of GR activity by PR-B was assessed by promoter-reporter assay in COS1 and U2OS cells over-expressing GR and PR and stimulated with GR- and/or PR-specific ligands. Association of GR and PR-B was measured by co-immunoprecipitation in COS1 and MCF-7 cells, while co-localization of GR and PR-B was measured by confocal microscopy and super-resolution structured illumination microscopy in COS1 cells. MPA significantly increased HIV-1 infection in both PBMCs and TZM-bl cells, while luteal phase hormones did so to a lesser extent. However, MPA but not luteal phase hormones increased the ratio of CD4+/CD8+ T cells in PBMCs. MPA but not luteal phase hormones also increased CCR5 protein expression on CD4+ T cells in PBMCs and total CCR5 mRNA expression in TZM-bl cells. In addition, MPA but not luteal phase hormones increased activation of CD4+ T cells in PBMCs. Using a GR antagonist or GR siRNA, it was shown that the GR but not PR-B is required for MPA-, but not luteal phase hormone-induced increased HIV-1 infection in PBMCs and TZM-bls. The presence of PR-B altered the anti-inflammatory, GR-mediated regulation of some key immunomodulatory genes, including GILZ and IL-6, in End1/E6E7 and HeLa cells in response to MPA. In general, basal (unliganded) expression of immunomodulatory genes exhibited a pro-inflammatory profile in the presence of PR-B. Co-immunoprecipitation assays showed that GR and PR-B appeared to associate. Confocal microscopy suggested GR and PR co-localized in the nucleus in response to GR- and/or PRspecific ligands, while super-resolution microscopy showed that co-localization occurred in select regions within the nucleus. Taken together, MPA increases HIV-1 infection in a manner different from that of luteal phase hormones, most likely involving increased CD4+ T cell frequency (CD4+/CD8+ ratio), activation and increased expression of CCR5 on CD4+ T cells, and requiring the GR. Furthermore, PR-B modulates GR-mediated immune function gene regulation, via potential association and region-specific nuclear co-localization. This suggests that the relative levels of GR/PR may play an important role in determining the inflammatory and immune responses and HIV-1 infection in HIV-1 target cells, both in DMPA users and women not using hormonal contraception.